2016
DOI: 10.1038/mp.2016.77
|View full text |Cite
|
Sign up to set email alerts
|

Autism with intellectual disability is associated with increased levels of maternal cytokines and chemokines during gestation

Abstract: Immune abnormalities have been described in some individuals with autism spectrum disorders (ASD) as well as their family members. However, few studies have directly investigated the role of prenatal cytokine and chemokine profiles on neurodevelopmental outcomes in humans. In the current study, we characterized mid-gestational serum profiles of 22 cytokines and chemokines in mothers of children with ASD (N=415), developmental delay without ASD (DD) (N=188), and general population (GP) controls (N=428) using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
199
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(212 citation statements)
references
References 48 publications
9
199
1
3
Order By: Relevance
“…A subsequent study found that maternal infections diagnosed in a hospital setting, presumably associated with more severe infections, were associated with an increased risk of ASD, while infections diagnosed in outpatient settings were not associated ASD (23). Quantification of cytokines, chemokines and other inflammatory markers obtained from archived maternal sera (24, 25) and amniotic fluid (26, 27) lends further support to the link between maternal infection and increased ASD risk, though studies have yielded mixed results (28, 29). Although there is a clear need for additional epidemiological studies, the current data suggest that, at least for a subset of women, exposure to infection during pregnancy may increase the risk of ASD or other CNS disorders (30, 31).…”
Section: Prenatal Immune Challenge In Humansmentioning
confidence: 88%
“…A subsequent study found that maternal infections diagnosed in a hospital setting, presumably associated with more severe infections, were associated with an increased risk of ASD, while infections diagnosed in outpatient settings were not associated ASD (23). Quantification of cytokines, chemokines and other inflammatory markers obtained from archived maternal sera (24, 25) and amniotic fluid (26, 27) lends further support to the link between maternal infection and increased ASD risk, though studies have yielded mixed results (28, 29). Although there is a clear need for additional epidemiological studies, the current data suggest that, at least for a subset of women, exposure to infection during pregnancy may increase the risk of ASD or other CNS disorders (30, 31).…”
Section: Prenatal Immune Challenge In Humansmentioning
confidence: 88%
“…Most recently, studies have demonstrated that elevated mid-gestational levels of inflammatory cytokines and chemokines are more highly associated with the ASD subphentoype that presents with intellectual disability (ID), compared with ASD without ID, developmental delay (DD) without ASD, and typically developing controls (Jones et al, 2016). These included higher levels of GM-CSF, TNF-α, IFN-γ, IL-1α, IL-1β, IL-4, and IL-6.…”
Section: Cytokinesmentioning
confidence: 99%
“…Perhaps the strongest association between an environmental factor and ASD has been found with maternal infection [94]. Studies in humans and in various animal species have indeed evidenced that maternal immune activation (MIA), due to viral or bacterial infection, increases neuroinflammation in the placenta and in the fetal brain, leading to offspring that display ASD-like behaviors [9598]. As discussed in a further section, several effects seen in MIA are also found upon developmental exposure to air pollution.…”
Section: Developmental Exposure To Air Pollution and Autism Spectrum mentioning
confidence: 99%